Sistem Informasi Monitoring Pelaporan Alsintan Tingkat Kecamatan Pada Kelompok Tani Di Kabupaten Jombang - Tholib hariono; Wilda prayoga (JOURNAL SAINS STUDENT RESEARCH, 2025)
The reporting process for agricultural machinery (Alsintan) by farmer groups (Poktan) and farmer group associations (Gapoktan) in Jombang Regency is still centralized at the district level, resulting in slow evaluations and suboptimal supervision. This study aims to design and implement a web-based information system that enables sub-district-level monitoring of Alsintan reporting. The system was developed using the Waterfall method, which includes stages of needs analysis, system design, implementation, testing, and maintenance. Key features include report submission by Poktan/Gapoktan and a monitoring dashboard for sub-district officers. The system was tested using the Blackbox Testing method to ensure that all functions operated properly. The results show that the system is effective in facilitating Alsintan reporting and monitoring at the sub-district level. It not only accelerates the reporting and data recapitulation process but also enhances accountability and decision-making efficiency by the Department of Agriculture through real-time, data-driven insights.